Description of Knowledge, Attitude, and Practice of Coronavirus Disease-19 Prevention Based on Gender and Age in Java Island Community - Alya Amarie; Ari Udijono; Nissa Kusariana; Lintang Dian Saraswati (Journal of Public Health for Tropical and Coastal Region, 2020)
Background: Coronavirus Disease 2019 (COVID-19) is an emerging respiratory disease that was first detected in Wuhan, China in December 2019 and has become a public health problem around the world. The main mode of transmission of this virus is human to human transmission via respiratory droplets that produced when a person coughs, sneezes, or talks. This virus spread rapidly from China to other countries. The participation of society is needed in reducing the spread of COVID-19. People's commitment and obedience in dealing with this pandemic situation are generally influenced by knowledge, attitudes and practices. In previous studies, it was found that gender and age affect the level of knowledge, attitudes, and practices for preventing COVID-19. This study aimed to assess knowledge, attitudes and practices towards COVID-19 prevention based on gender and age group in Java Island residents. Methods: This study used a quantitative descriptive method with a cross-sectional study design. The sampling technique used is non-probability sampling. The number of samples in this study was 1,680 Java Island residents. Results: The variables in this study were measured through a self-reported questionnaire that was distributed online. The results showed that the female and the late adult group (≥61 years) tended to have good knowledge and practice towards COVID-19 prevention.Conclusion : It is necessary to increase education related to COVID-19 and socialization of health protocols to the community with male sex and young age groups